Research of Current Common Languages in Afghanistan - Pohanyar Hejratullah Mobashir (Randwick International of Education and Linguistics Science Journal, 2021)
The Purpose of this academic article is to analyze the current languages of Afghanistan; in addition, the position is studied. Afghanistan has a diverse cultural heritage, which is protected by these languages; the importance of keeping it alive is very high. This research is descriptive and analytical the type of research is librarian and methodical, which is a description of the current popular languages. In this country current languages and dialects thirty summers, each language is based on the number of speakers has its own status and position, which are called official, residual, local and national languages. These languages belong to the most popular groups in the world the famous are Aryan, Indo-Aryan and Turkish. In addition, the languages of the pro- semiotic and seraiki groups are currently in question.